2001
DOI: 10.1046/j.1365-313x.2001.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐activation of Brassica napus BN115 promoter is mediated by structural changes in membranes and cytoskeleton, and requires Ca2+ influx

Abstract: SummaryPrevious studies on cold-triggered events leading to Ca 2+ in¯ux during cold acclimatization have been conducted on either unicellular cyanobacterium Synechocystis or plant cell suspensions, and used transcript levels of cold-induced genes as end-point markers. Whether the results of these studies are valid for intact plants or their organs is not known. Here we examine cold signaling in transgenic Brassica napus seedlings carrying, in addition to the endogenous cold-inducible BN115 gene, the b-glucuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(165 citation statements)
references
References 41 publications
4
161
0
Order By: Relevance
“…However, a more subtle explanation can be suggested based on the fact that microtubule polymer status is also known to be related to adaptive responses. For example, many environmental triggers, such as cold and osmotic stress, are associated with the reorganization of the cytoskeleton (Blancaflor and Hasenstein, 1995;Sangwan et al, 2001;Wojtaszek et al, 2007). The recent discovery that a receptor-like kinase may act as a cell wall integrity sensor suggests that internal as well as external stresses could be an aspect of the adaptive response (Hématy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, a more subtle explanation can be suggested based on the fact that microtubule polymer status is also known to be related to adaptive responses. For example, many environmental triggers, such as cold and osmotic stress, are associated with the reorganization of the cytoskeleton (Blancaflor and Hasenstein, 1995;Sangwan et al, 2001;Wojtaszek et al, 2007). The recent discovery that a receptor-like kinase may act as a cell wall integrity sensor suggests that internal as well as external stresses could be an aspect of the adaptive response (Hématy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…ies have previously shown that changes in membrane fluidity appear to be a potential mechanism for the sensing of cold temperatures in higher plants as well (57)(58)(59)(60). As proposed for bacterial Hik33 (61), it can be speculated that the plant AHK proteins might utilize a similar mechanism for the detection of cold temperatures.…”
Section: Cold Perception Of the Ahk Proteins As A Primary Response Domentioning
confidence: 94%
“…Many signal molecules can improve plant tolerance to low temperature stress by altering the expression levels of COR, CBFs and ICE1 genes. For example, ethylene molecules negatively regulate cold tolerance by repressing expression of CBFs [25]. Inositol 1, 4, 5-trisphosphate (IP3) and Ca 2+ induce CBFs and COR expression in plant [25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ethylene molecules negatively regulate cold tolerance by repressing expression of CBFs [25]. Inositol 1, 4, 5-trisphosphate (IP3) and Ca 2+ induce CBFs and COR expression in plant [25]. NO positively regulate the expression of cold related genes COR15a, LT130 and LTI78 in Arabidopsis under low temperature conditions [17].…”
Section: Introductionmentioning
confidence: 99%